2019
DOI: 10.1108/jrit-03-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

Educators’ perceptions of technology integration into the classroom: a descriptive case study

Abstract: Purpose The purpose of this paper is to supply an in-depth description of the educators’ values, beliefs and confidence changing from a traditional learning environment to a learning environment integrating technology. Design/methodology/approach The descriptive case study design was employed using descriptive statistical analysis and inductive analysis on the data collected. Findings Themes on a high level of confidence, the importance of professional development and training, self-motivation, and excitem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 27 publications
4
50
0
Order By: Relevance
“…Mitchell and Vidal (2001) and Richards and Rogers (2001) believe that approaches and methods in second language teaching have both dynamics and diversity. In other words, advancements in socio-cultural theory (Van Boxtel, Van der Linden, & Kanselaar, 2000;Van de Pol, Mercer, & Volman, 2019), educationalpsychological theory (VanPatten; Vallori, 2014;Wittwer & Renkl, 2008), neuroscience (Benati & Rastelli, 2018;), and technological advancements (Brown, 2009;Hartman, Townsend, & Jackson, 2019;Leutner, 2019;Rassaei, 2018) have made changes to human perceptions and conceptions of effective second language teaching. These advancements, eventually, turn into innovations in research and practices in second language teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell and Vidal (2001) and Richards and Rogers (2001) believe that approaches and methods in second language teaching have both dynamics and diversity. In other words, advancements in socio-cultural theory (Van Boxtel, Van der Linden, & Kanselaar, 2000;Van de Pol, Mercer, & Volman, 2019), educationalpsychological theory (VanPatten; Vallori, 2014;Wittwer & Renkl, 2008), neuroscience (Benati & Rastelli, 2018;), and technological advancements (Brown, 2009;Hartman, Townsend, & Jackson, 2019;Leutner, 2019;Rassaei, 2018) have made changes to human perceptions and conceptions of effective second language teaching. These advancements, eventually, turn into innovations in research and practices in second language teaching.…”
Section: Introductionmentioning
confidence: 99%
“…This finding answers the query of the digital literacy owned by the teacher. Having been able to use various apps, the teachers are capable, and thus they are more confident when using technologies in the classroom (Hartman, Townsend, and Jackson, 2019). Thus far, the study has found that the teachers are prepared based on the respondents' feedback and are considered will be comfortable when using various apps when organizing either online or offline class during this emergency remote teaching and learning condition.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits are made possible because technologies are equipped with features such as multimedia interfaces that help language learning (Moura and Carvalho, 2011). As a result, most of the studies promote the use of technology in the classroom (Gomes, Lopes, and Araujo, 2016;Mondahl and Razmerita, 2014;Hartman, Townsend, and Jackson 2019). Several studies also find that technology improves learning qualities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations